2012
DOI: 10.1007/s00213-012-2903-x
|View full text |Cite
|
Sign up to set email alerts
|

Latent vulnerability in cognitive performance following chronic cocaine self-administration in rhesus monkeys

Abstract: Rationale Cocaine use is associated with cognitive impairment which impacts treatment outcome. A clearer understanding of those deficits, and whether particular environments exacerbate them, is needed. Objectives This study evaluated whether previously observed domain-specific cognitive deficits persisted following a three month cessation from chronic cocaine self-administration, as well as the impact of novel and cocaine-associated attentional distractors. Methods Control and experimental groups of monkey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…This view is supported by observations that exposure of animals to drugs can produce cognitive and neural alterations that resemble those that are exhibited by substance-dependent humans (Jentsch et al, 2002; Nader et al, 2006; Porter et al, 2011; Groman et al, 2012; Porter et al, 2012). The coupling of neural changes following drug exposure with alterations in cognition (Groman et al, 2012) underscores the functional impact of such changes on behavior.…”
Section: Introductionmentioning
confidence: 83%
“…This view is supported by observations that exposure of animals to drugs can produce cognitive and neural alterations that resemble those that are exhibited by substance-dependent humans (Jentsch et al, 2002; Nader et al, 2006; Porter et al, 2011; Groman et al, 2012; Porter et al, 2012). The coupling of neural changes following drug exposure with alterations in cognition (Groman et al, 2012) underscores the functional impact of such changes on behavior.…”
Section: Introductionmentioning
confidence: 83%
“…It should also be pointed out that latent cognitive deficits not apparent under standard conditions can exist. For example, with these same monkeys, we previously demonstrated that reversal impairments that had normalized upon cessation of cocaine re-emerged when attentional distractors were added to the task (Porter et al 2013). …”
Section: Discussionmentioning
confidence: 96%
“…The cocaine group was drug-free for 20 months prior to the start this study. During that time, they participated in behavioral studies that have been reported (Porter et al 2013), but did not undergo any drug exposure other than ketamine for TB testing or other routine clinical procedures. The animals are a subset of those used for a previous study of cognitive deficits associated with chronic cocaine self-administration (Porter et al 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Full details of the self-administration procedure for this cohort of monkeys have been published previously (Porter et al, 2013, 2011). Briefly, for 2 periods over a 5 year span (SA1: 12 months and SA2: 19 months separated by a 27 month period of abstinence), subjects in the cocaine group self-administered cocaine intravenously using an FR30 reinforcement schedule: up to 6 infusions 0.5 mg/kg/infusion each day 4 days/week (Tue-Fri) during SA1; the same schedule was used during the first part of SA2.…”
Section: Methodsmentioning
confidence: 99%
“…In the same monkeys self-administering cocaine from which we previously reported impairment of cognitive performance (Porter et al, 2013; Porter et al, 2011), we assessed if any disruptions in activity-based sleep efficiency were related to these cognitive impairments.…”
Section: Introductionmentioning
confidence: 99%